Implementation of the Hadith on Maintain the Cleanliness by Santri of Siti Fatimah Islamic Boarding School, Kanggraksan: Implementasi Hadis Menjaga Kebersihan oleh Santri Pondok Pesantren Siti fatimah, Kanggraksan - Fatimaturrohmah; Anis, Anisatun Muthi'ah; Lukman Zain M Sakur; Alfian Febriyanto (Jurnal Living Hadis, 2023)
The issue of cleanliness is one aspect that Islam pays great attention to. This can be seen from several Al-Qur'an texts and hadiths which equate the level of cleanliness with a person's faith, so it is appropriate for Muslims to implement clean living behavior in their daily lives, especially students in Islamic boarding schools. This article explains the existence of various religious texts regarding cleanliness which are studied by santri through recitation with two basic questions; first, what is the knowledge of the Siti Fatimah Islamic Boarding School students regarding cleanliness traditions?; and second, does the students' knowledge of the hadith on cleanliness have a relationship with clean living behavior? These questions were then studied using quantitative methods with a correlational approach and analyzed using the theory of reasoned action. The results of this research show that there is no significant relationship between knowledge of cleanliness hadiths and clean living behavior of Siti Fatimah Islamic Boarding School students. Based on the analysis of the theory of reasoned action, the santri's clean living behavior is purely a behavior, there are no other influencing factors.